EFFECTIVENESS OF BEMO: AN ANDROID-BASED EDUCATIONAL GAME AS A LEARNING MEDIA ON MOLECULAR SHAPE MATERIAL - Vinna Rahma Jazila; Achmad Lutfi (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2024)
This study analyzes the effectiveness of the android-based BEMO game as a learning media on molecular shape material. The trial in this study was conducted on one of the XI classes at SMA Kartika IV-3 Surabaya, namely class XI E with 30 students. Effectiveness is based on pretest and posttest results comprising 15 questions and questionnaire results comprising 12 statements. Learning outcomes were analyzed with the help of the SPSS program, while the questionnaire results were analyzed by quantitative description. The results of the analysis with the help of SPSS show that the use of the android-based BEMO game as a learning media on molecular shape material is effective for improving student learning outcomes by conducting the Paired Samples T-Test test which is known t table with df = 29, α 5% = 1.669 while t count = 26.133. This shows a significant difference in students' learning outcomes on molecular shape material between the pretest and posttest. The posttest results were also analyzed with classical completeness getting a percentage of 86.67%. Based on the data obtained from the students' response questionnaire, it is known that students feel happy to learn when using the BEMO game so that students can participate actively, have increased concentration and willingness to learn and feel comfortable when undergoing the learning process. Based on this data, it can be concluded that using android-based BEMO game as a learning media on molecular form material is effective in significantly improving students' learning outcomes